The complete mitochondrial genome of the pentastomid Armillifer grandis (Pentastomida) from the Democratic Republic of Congo. Issue 1 (1st January 2017) - Grau, José Horacio; Dunlop, Jason A.; Meixner, Martin; Tappe, Dennis
Abstract: We present the first complete mitochondrial genome of the pentastomid Armillifer grandis (Arthropoda: Pentastomida) collected from the lungs of a rhinoceros viper ( Bitis nasicornis ) in the Democratic Republic of Congo. The full length mitochondrial genome of Armillifer grandis, which measures 16, 073 bp in length, contains 13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes. A clear A + T bias is observed in the mitogenome of Armillifer grandis with an overall base composition of 34.6% A, 29.4% T, 29% C, and 6.9% G, and a GC content of 35.9%. The gene arrangement is identical to that of previously described pentastomid mitogenomes.